Immune Thymic Profile of the MOG-Induced Experimental Autoimmune Encephalomyelitis Mouse Model - das Neves, Sofia P.; Serre-Miranda, Cláudia; Nobrega, Claudia; Roque, Susana; Cerqueira, João J.; Correia-Neves, Margarida; Marques, Fernanda (Frontiers in Immunology, 2018)
Multiple sclerosis (MS) is a chronic, immune-mediated, demyelinating disease that affects the neurons of the central nervous system. Activated T cells, specific for myelin epitopes, cross the brain barriers and react against the myelin sheath, leading to demyelination. Since T cells are generated within the thymus, here we explored, in mice, the alterations occurring in this organ throughout the different phases of the disease. We induced experimental autoimmune encephalomyelitis (EAE) in C57BL/6 females and sacrifice them at the onset (day 16) and chronic phases of disease (day 23), along with non-induced controls. We observed thymic atrophy in EAE mice at the onset that remained until the chronic phase of disease. This atrophy was associated with a preferential loss of the CD4+CD8+ double positive thymocytes, an intermediate population between the more immature CD4-CD8- double negative and the most mature single positive thymocytes. This was accompanied by an increase in the thymic medullary/cortical ratio and by an altered expression levels of genes important for T cell survival. During the chronic phase, the thymi remained atrophic, but reacquired the normal proportion of the main four thymocyte populations and the normal medullary/cortical ratio. Importantly, at the onset phase, and accompanying these thymic alterations, EAE animals presented an increased percentage of demyelinating lesion area in the cerebellum, and an increased expression of interferon gamma (Ifng), interleukin (Il) 12a and Il17a. This study suggests dynamic thymic alterations occurring in response to EAE, from the induction to the chronic phase, that might help to elucidate the MS pathophysiology.